ANALISIS PENGARUH KEPEMILIKAN INSTITUSIONAL, FREE CASH FLOW, INVESTMENT OPPORTUNITY SET TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVENING ( Studi Kasus pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Perio - Purwanto Putri, Ginza Angelia; Chabachib, Mohammad (Faculty of Economics and Business Diponegoro University, 2013)
The purpose of this research is to analyze the effects of Institutional Ownership, Free Cash Flow, and Investment Opportunity Set toward Firm Value through Debt Policy as Intervening variable. Independent Variables in this research are Institutinal Ownership, Free Cash Flow, and Investment Opportunity Set. Intervening Variable is Debt Policy and dependent variable is Firm Value.The sample determinity method is Purpose Sampling method. Samples in this research are non financial companies in Bursa Efek Indonesia (BEI) period of 2008-2011 which amounts to 103 companies. The analysis technique in this research is Structural Equation Model.Based on Structural Equation Model test, the models was filled the goodness of fit criteria. According to result, institutional ownership has a positive and significant effect on firm value, so that hypothesis 1 is accepted. Institutional ownership has a negative and significant effect on debt policy,so that hypothesis 2 is accepted. Free cash flow has apositive and significant impact on debt policy, so that hypothesis 3 is accepted. Investment opportunity set has a negative and significant impact on debt policy, so that hypothesis 4 is accepted. Investment opportunity set has a positive and significant effect to firm value, so that hypothesis 5 is accepted. Debt policy has a negative and significant effect to firm value, so that hypothesis 6 is accepted. Direct effect of Institutional ownership (X1) to firm value (Y) isÂ Â 0.175 and indirect effect institutional ownership (X1) effect to value of the company (Y) through the debt policy (X4) is 0.037 , direct effect is higher than indirect effect so that hypothesis 7 is rejected. Direct effect of Investment opportunity set (X3) to firm value (Y) is 0.153, and indirect effect Investment opportunity set (X3) to firm value (Y) through debt policy (X4) is 0.0674. Direct effect is higher than indirect effect so that hypothesis 8 was rejected